National and cultural activities of the Tatar diaspora in the North Western China in the first half of the XX century: theater and string orchestra - Gulnaz Nazymovna Khisamieva (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the study lies in the fact that the national and cultural life of the Tatar diaspora in the Northwest China has not been the subject of the research. The research interest is also caused by the fact that the history of the formation and development of the Tatar diaspora, everyday, spiritual, educational and cultural life has not been studied at all and is of particular interest to researchers. The scientific novelty of the work lies in the fact that the article examines the process of formation of Tatar theaters and string orchestras in the cities of Kuldzha and Chuguchak for the first time, where the bulk of Tatar emigrants lived. Particular attention was paid to the role of Tatar theaters in the life of indigenous and visiting peoples of the XUAR of the PRC. The purpose of the work is to study and systematize the national and cultural life of the Tatars of Xinjiang. As a result of the study, it can be concluded that the creation of theaters and string orchestras has contributed to the rallying of the Tatars, as well as the preservation of the native language, literature, traditions, culture and identity of the people, which is also a very important factor in preserving identity among the local population of Xinjiang.